Lemongrass essential oil nanoemulsion formulations based on tragacanth gum and guar gum as durable anti-mosquito fabric finishing agents - Azlan bin Kamari, Norjan binti Yusof (Tanjung Malim, 2024)
Lemongrass essential oil nanoemulsion formulations based on tragacanth gum and guar gum as durable anti-mosquito fabric finishing agents by Azlan bin Kamari, Norjan binti Yusof